SISTEM PAKAR DIAGNOSA GANGGUAN KEHAMILAN BERBASIS WEB PADA KLINIK PRATAMA ANDRIANI MEDIKA BEKASI - Riska Utami Dewi; Herlawati; Adi Supriyatna (Jurnal Teknik Informatika, 2015)
Abstract— Pregnant women sometimes experience health problems during their pregnancy, pregnant women tend to experience symptoms different from normal pregnancies experienced by pregnant women. The risk of maternal mortality is caused by several factors, namely late to recognize the danger, delay the decision to be referred, late coming to the health facility and late to get adequate services by health workers. Coverage of relatively low relief from health professionals coupled with obstetric health services are very limited, so not able to cope with high-risk pregnant women, lack of information about the symptoms that arise during pregnancy and the dangers of high risk of pregnancy to be one of the risk of maternal mortality. The method used in this thesis is the method of Forward Chaining. This method provides a diagnosis of a disorder of pregnancy based on the symptoms that were collected at the consultation stage. The purpose of this research is to design a pregnancy disorder diagnosis expert system based on the web Andriani Primary Medical Clinic Bekasi to be useful for the wider community and improve the quality of service that is clear about interruption of pregnancy in order to provide appropriate action or treatment. The system is designed to get a good response and can help in the diagnosis of disorders of pregnancy more quickly experienced by pregnant women.